Tn1721-encoded tetracycline resistance: mapping of structural and regulatory genes mediating resistance. - Altenbuchner, J (1983)
The genes encoding inducible tetracycline resistance in Tn1721 were located in a 2.1-kilobase portion of the transposon. Using deletions and insertions, we mapped and characterized two tet genes by their mutant phenotypes. Two tetracycline-inducible polypeptides synthesized in minicells were assigned to the tet genes. The polarity of the tet genes was determined by employing a deletion and a gene fusion which altered the carboxy termini of the polypeptides. The gene responsible for resistance (tetA) encompasses 1,250 base pairs and encodes a membrane-bound protein with an apparent molecular weight of 34,000. The second gene (tetR) encompasses at least 650 base pairs and encodes a soluble 26,000-dalton protein, identified by complementation analysis as the repressor. The two adjacent genes have opposite transcriptional polarity, suggesting that the sites controlling their expression are located in the intercistronic region between tetA and tetR.